Α-Cyclodextrin – Water binary system. New data on dehydration of α-cyclodextrin hexahydrate. (October 2016) - Manakov, Andrey Yu.; Rodionova, Tatyana V.; Aladko, Lyudmila S.; Villevald, Galina V.; Lipkowski, Janusz S.; Zelenina, Lyudmila N.; Chusova, Tamara P.; Karpova, Tamara D.
Graphical abstract: Highlights: The T, x – phase diagram of α -CD – water binary system was studied by DTA and DSC. PXRD was used to follow structural transformation of α -CD hydrates. α -CD·6.1H2 O transforms into α -CD·5.3H2 O at the temperature ∼355 K in isochoric conditions. The solid solution on the base of α -CD·6H2 O Form I is formed within the limits of α -CD·6.1H2 O – α -CD·2.1H2 O. Abstract: Cyclodextrins (CDs) are torous-like macrocycles composed of glucopyranose units. Due to their shapes, they are capable to include a wide variety of organic and inorganic guest molecules with formation of inclusion complexes in solid and liquid state. CDs crystallize from aqueous solution as hydrates (water molecules are located in the cavities and fill intermolecular space). The process of inclusion complex formation is, in fact, a replacement reaction of water molecules by hydrophobic guest molecules. Given the important role of water in the formation of CDs inclusion complexes, and the fact that the main commercial forms of cyclodextrins are the hydrated ones, the study of temperature ( T ) – composition ( x ) phase diagram of cyclodextrin – water binary system is of scientific and practical interest. This article reports an experimental study of the T, x – phase diagram of α -cyclodextrin – water binary system under isochoric conditions by differential thermal analysis (DTA) and differential scanning calorimetry (DSC). Powder X-ray diffraction was used to identify the structures of different α -CD hydrates and to follow their phase transformations. It was shown that dehydration processes in isochoric and isobaric (open air) conditions differ significantly. In the temperature range of approximately 351 K–359 K the α -CD hexahydrate of known Form I structure transforms into the α -CD·5.3H2 O of unknown structural type. It is found that the solid solution on the base of the structure α -CD hexahydrate Form I is formed within the limits of α -CD·6.1H2 O – α -CD·2.1H2 O. The above findings give new insight on dehydration processes in the α -CD – water binary system. Thermodynamic parameters of the dehydration process are derived from DSC data and tensimetric measurements of vapor pressure over α -CD·6.1H2 O by static method. The data obtained represent new and valuable information which can be very helpful when choosing conditions of the gas-phase synthesis of α -CD complexes.